IMPLEMENTASI PENELITIAN PERILAKU DALAM AKUNTANSI PADA PRAKTIK MANAJEMEN LABA: SYSTEMATIC LITERATURE REVIEW - Dimarizkya, Aliya; Munandar, Agus (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to systematically examine earnings management practices in Indonesia during the period 2020–2025 using the Systematic Literature Review (SLR) method. The findings indicate that earnings management in Indonesia remains significant and multidimensional, influenced by various external and internal factors. Externally, tax regulations, capital market pressures, and broader economic dynamics including the impact of the COVID-19 pandemic encourage companies to manipulate financial statements, particularly through revenue and expense recognition within the self-assessment tax system and earnings adjustments prior to quarterly reporting, IPOs, and other corporate actions. Internally, earnings management is driven by performance target pressures, managerial incentives, as well as weak corporate governance and low audit quality, especially among small audit firms that exhibit economic dependence on their clients.